PENGARUH MODEL THINK PAIR SHARE BERBANTUAN ARTIFICIAL INTELLIGENCE PADA MATERI WARISAN BUDAYA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Fadhilah, Khansa; Mahya Fanny, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students' understanding in the subject of science at SDN Keboananom is due to limited learning receiving explanations from teachers, so a model is needed that is able to involve students through the Think Pair Share model. This study aims to determine the effect of the Think Pair Share (TPS) learning model assisted by Artificial Intelligence on the critical thinking skills of fifth grade students in the subject of science. The study used a quantitative approach with a quasi-experimental Non-Equivalent Control Group Design. The sample determination used a random sampling technique by assigning V-A as the experimental class and V-C as the control class with a total of 28 students each. The research instrument was a posttest in the form of a description. Data analysis included the Shapiro-Wilk normality test, Levene's homogeneity test, and the Independent Samples T-Test hypothesis test. The results showed that the data were normally distributed and homogeneous and there were significant differences when tested t and tested the average. These findings indicate that the application of TPS assisted by Artificial Intelligence is effective in improving students' critical thinking skills. In addition, it can be an alternative innovative learning to improve the quality of science learning and encourage student activeness. The implications of this research provide recommendations for teachers to integrate AI technology in a planned manner to make learning more adaptive, interactive, and student-centered, thereby sustainably developing 21st-century skills.